Differences in the Bisection Line in the Improved Neubauer Counting Booth on the Appropriateness of Leukocyte Count - Sastra, Zidan Pramudya; Maharani, Eva Ayu; Astuti, Dewi (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Leukocyte count examination is an examination that is often performed in clinical laboratories. Leukocyte count examination can be performed using a hematology analyzer or counting chamber for manual methods. Leukocyte cell counting using the manual method must use a standardized counting chamber. Currently, a different type of Improved Neubauer counting chamber variation has been found from the standard type, namely the difference in the outer limit of the counting area. In the standard type counting chamber, the outer limit of the counting area has three lines, while in the variation type counting chamber there is only one line. The purpose of this study was to determine whether there was a difference in the dividing line of the Improved Neubauer counting chamber on the suitability of the leukocyte count between the standard Improved Neubauer counting chamber type and the variation type Improved Neubauer counting chamber. The research design used in this study was observational analytic (Cross-Sectional) with a sample size of 20 EDTA blood. The results of the study obtained normally distributed data. then the Dependent Parametric Test (Paired T-Test) was carried out with a confidence level of 95%. The results of the Paired T-test showed the Sig.(2-tailed) value was 0.000 (<0.05). The conclusion of the study was that there was a significant difference in the results of the leukocyte count between the use of the standard Improved Neubauer counting chamber and the variation Improved Neubauer counting chamber. The use of the standard Improved Neubauer counting chamber is more recommended than the variation Improved Neubauer counting chamber.